Rancang Bangun Sistem Informasi Penilaian Kinerja UMKM Pada LPB-YDBA Astra Waru - Renata, Christy Mitha; Widodo, Arifin Puji; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
The purpose of LPB-YDBA Astra Waru is to help SMEs to be "independent”, develop, and empower the local economy through entrepreneurial efforts, and aims to assist the implementation of the 5 pillars formed by PT Astra International, Tbk namely UMKM/IGA (International Grade Astra) program.Corporate performance appraisal basically is a crucial factor in order to develop an effective and efficient organization, its purpose is to provide an assessment as the basis for a reward, making a decision, and is used as a basis for evaluating achievement. At this performance appraisal, every SMEs is given the opportunity to get a reward from PT Astra International, Tbk and is facilitated the access to get capital borrowing at PT Astra International, Tbk companies such as Bank Permata and United Tractors (UT). SMEs will be assessed by a questionnaire that based on five pillars and collect some of the required financial statements to calculate the financial ratios.There are obstacles in the performance assessment carried out, because in the performance appraisal there is a process for assessing the financial ratios calculation of financial terms, while there is no system that helps in calculating the financial value. As a result, the grade-level in the performance appraisal report does not appear to be true and results in the performance appraisal is invalid.From the implementation of information systems implemented in LPB-YBDA Astra, it can be concluded that the system created can accelerate the process of performance appraisal of SMEs. Information systems of SMEs performance appraisal can be used to help the LPB-YDBA Astra in evaluating the performance appraisal of SMEs that took place on LPB-YDBA Astra.